8 PULMONARY ARTERY HEMODYNAMICS IN LOW- AND HIGH-ALTITUDE NATIVE ETHIOPIANS. (1st March 2007) - Hoit, B. D.; Dalton, N.; Erzurum, S. C.; Janocha, A.; Beall, C. M.
Abstract : Background: Indigenous high-altitude populations have distinctive biologic characteristics that appear to be adaptive. Thus, although evidence suggests that homogeneous and genetically distinct populations in the Andean and Tibetan Highlands have adapted differentially their pulmonary hemodynamics to high-altitude stress, the situation for the third major high-altitude area, Ethiopia, is unknown. Objectives and Methods: Accordingly, we examined noninvasively pulmonary arterial hemodynamics using Doppler echocardiography (MyLab30CV, Biosound Esaote, Inc.) in 193 healthy, nonsmoking, male and nonpregnant female Amharic adults, 18 to 55 years of age, from the Semien Mountain Region of NW Ethiopia native to high (3, 900 m) or low (1, 200 m) altitudes and 51 matched US sea-level native resident controls (240 m). Standard parasternal, apical, and subcostal two-dimensional views were obtained and color flow-directed pulsed-wave Doppler of transvalvular flows and continuous-wave Doppler of the tricuspid regurgitant flow were measured. An adequate tricuspid regurgitant jet gradient (TRgrad) was obtained in 71% of Ethiopians and in 92% of controls. The TRgrad and the velocity-time integral of right ventricular outflow (RVOTvti) were used as surrogates of pulmonary artery pressure and pulmonary blood flow, respectively, and pulmonary vascular resistance indexed to body surface area (PVRi) was calculated using a validated method using the TRgrad and the RVOTvti.Results(seeTable ):High-altitude native residents had significantly higher pulmonary artery systolic pressures than low-altitude natives and sea-level controls. Moreover, compared with the sea-level controls, high-altitude natives had significantly higher pulmonary blood flow, hemoglobin (Hb) level, and arterial oxygen content and lower PVR and Hb saturation. Conclusions: We conclude that (1) pulmonary artery pressure is higher in native high-altitude Ethiopians but is generally mild and offset by pulmonary vascular resistance; (2) the Ethiopian adaptation to high altitude involves increased pulmonary blood flow and arterial oxygen delivery. Funding from an NSF grant (0452326) to C.M.B. and ASE Sonographer grant to N.D.